Safety, Adherence and Persistence in a Real-World Cohort of German MS Patients Newly Treated With Ocrelizumab: First Insights From the CONFIDENCE Study - Weber, Martin S.; Buttmann, Mathias; Meuth, Sven G.; Dirks, Petra; Muros-Le Rouzic, Erwan; Eggebrecht, Julius C.; Hieke-Schulz, Stefanie; Leemhuis, Jost; Ziemssen, Tjalf (Frontiers in Neurology, 2022)
Background: Real-world relapsing multiple sclerosis (RMS) and primary progressive MS (PPMS) populations may be more diverse than in clinical trials. Here, we present a first analysis of safety, adherence and persistence data from a real-world cohort of patients newly treated with ocrelizumab. Methods: CONFIDENCE (ML39632, EUPAS22951) is an ongoing multicenter, non-interventional post authorization safety study assessing patients with RMS or PPMS newly treated with ocrelizumab or other disease-modifying therapies for up to 10 years. For this analysis, patients newly treated with ocrelizumab were analyzed in subgroups by MS phenotype and age over a mean ~1 year of exposure totaling 2,329 patient years [PY]). Results: At data cutoff (14 October 2020), 1702 patients with RMS and 398 patients with PPMS were treated with ≥1 dose of ocrelizumab. At baseline, the mean ages (SD) of patients with RMS and PPMS were 41.59 (11.24) and 50.95 (9.88) years and the mean EDSS (Expanded Disability Status Scale) was 3.18 (1.87) and 4.41 (1.59), respectively. The most common adverse events (AEs) and serious AEs across both phenotypes were infections and infestations, with infection SAE rates of 2.8 events/100 PY and 1.5 events/100 PY in patients with RMS and PPMS, respectively. Across all phenotypes, ocrelizumab persistence was 92% at 24 months; median time between doses was ~6 months. Conclusions: The ocrelizumab safety profile observed in the CONFIDENCE real-world MS population was consistent to the one observed in pivotal clinical trials. High treatment persistence and adherence were observed.